Analisis Faktor Faktor yang berhubungan dengan Pelaksanaan Pendidikan Kesehatan Oleh Perawat di Ruang Rawat Inap RS PMC - Awaliyah Ulfah Ayudytha Ezdha; Ummu Habibah; Dwi Elka Fitri (LPPM Universitas Muhammadiyah Riau, 2019)
ABSTRACT The hospital as a provider of health services in the form of maintaining and improving health and aims to achieve optimal health status for the community. One indicator of the quality of nursing services is whether the nursing services provided are satisfying the patient or not. One of the roles performed by nurses is to carry out health education in discharge planning for patients in the inpatient room. Health education is very important to be carried out by a nurse. The purpose of this study was to analyze the factors related to the implementation of health education by nurses in the Inpatient at PMC Hospital. The research design used is a quantitative method with analytic cross-sectional study design. This research was conducted at Pekanbaru Medical Center Hospital with a sample of 35 nurses on duty at the hospital according to inclusion criteria. From the results of the study found factors related to the implementation of health education by nurses in the inpatient room of the PMC Hospital : Length of Work (p value 0.010), Training attended (p value = 0,000) and Level of Knowledge (p value = 0.002). This means that factors related to the implementation of health education by nurses must be maintained and considered by management to improve the implementation of health education by nurses so that the quality of service and satisfaction can be improved.